Health and cognition among adults with and without Traumatic Brain Injury: A matched case–control study. (23rd February 2022) - Kumar, Raj G.; Ketchum, Jessica M.; Hammond, Flora M.; Novack, Thomas A.; O'Neil-Pirozzi, Therese M.; Silva, Marc A.; Dams-O'Connor, Kristen
ABSTRACT: Objectives: To evaluate associations between traumatic brain injury (TBI) and presence of health conditions, and to compare associations of health and cognition between TBI cases and controls. Methods: This matched case–control study used data from the TBI Model Systems National Database (TBI cases) and Midlife in the United States II and Refresher studies (controls). 248 TBI cases were age-, sex-, race-, and education-matched without replacement to three controls. Cases and controls were compared on prevalence of 18 self-reported conditions, self-rated health, composite scores from the Brief Test of Adult Cognition by Telephone. Results: The following conditions were significantly more prevalent among TBI cases versus controls: anxiety/depression (OR = 3.12, 95% CI: 2.20, 4.43, p < .001), chronic sleeping problems (OR = 2.76, 95% CI: 1.86, 4.10, p < .001), headache/migraine (OR = 2.61, 95% CI: 1.50, 4.54, p = .0007), and stroke (OR = 6.42, 95% CI: 2.93, 14.10, p < .001). The relationship between self-rated health and cognition significantly varied by TBI ( p interaction = 0.002). Conclusion: Individuals with TBI have greater odds of selected neurobehavioral conditions compared to their demographically similar uninjured peers. Among persons with TBI there was a stronger association between poorer self-rated health and cognition than controls. TBI is increasingly conceptualized as a chronic disease; current findings suggest post-TBI health management requires cognitive supports.